Copper-Catalyzed N–N Bond Formation by Homocoupling of Ketoximes via N–O Bond Cleavage: Facile, Mild, and Efficient Synthesis of Azines - Zhao, Mi-Na; Liang, Hao; Ren, Zhi-Hui; Guan, Zheng-Hui (Synthesis, 2012)
A facile, mild, and efficient copper-catalyzed homocoupling of ketoximes involving N–O bond cleavage in the presence of sodium bisulfite (NaHSO3) has been developed. This reaction shows good functional group tolerance and affords a broad scope of azines in high yields.
Keywords: copper; homocoupling; ketoxime; azine; NaHSO3